음이온 교환막 수전해용 Fe-Ni-Pt 나노촉매 제조 및 특성 - 이재영(JAEYOUNG LEE); 이홍기(HONGKI LEE) (한국수소 및 신에너지학회 논문집, 2023)
Fe-Ni-Pt nanocatalysts were loaded on carbon black powders which were synthesized by a spontaneous reduction reaction of iron (II) acetylacetonate, nickel (II) acetylacetonate and platinum (II) acetylacetonate. The morphology and the loading weight of Fe-Ni-Pt nanoparticles were characterized by transmission electron microscopy and thermogravimetric analyzer. The amount of Fe-Ni-Pt catalyst supported on the carbon black surface was about 6.42-9.28 wt%, and the higher the Fe content and the lower the Pt content, the higher the total amount of the metal catalyst supported. The Brunauer-Emmett-Teller Analysis (BET) specific surface area of carbon black itself without metal nanoparticles supported was 233.9 m2/g, and when metal nanoparticles were introduced, the specific surface area value was greatly reduced. This is because the metal nanocatalyst particles block the pore entrance of the carbon black, and thereby the catalytic activity of the metal catalysts generated inside the pores is reduced. From the I-V curves, as the content of the Pt nanocatalyst increased, the electrolytic properties of water increased, and the activity of the metal nanocatalyst was in the order of Pt > Ni > Fe.